2020
DOI: 10.3389/fcell.2019.00328
|View full text |Cite
|
Sign up to set email alerts
|

Forged by DXZ4, FIRRE, and ICCE: How Tandem Repeats Shape the Active and Inactive X Chromosome

Abstract: Recent efforts in mapping spatial genome organization have revealed three evocative and conserved structural features of the inactive X in female mammals. First, the chromosomal conformation of the inactive X reveals a loss of topologically associated domains (TADs) present on the active X. Second, the macrosatellite DXZ4 emerges as a singular boundary that suppresses physical interactions between two large TADdepleted "megadomains." Third, DXZ4 reaches across several megabases to form "superloops" with two ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 91 publications
(152 reference statements)
0
13
0
Order By: Relevance
“…Previous studies have shown that the active and inactive X chromosome have strikingly different 3D conformations (Bansal et al, 2019;Deng et al, 2015;Giorgetti et al, 2016;Minajigi et al, 2015;Nora et al, 2012;Rao et al, 2014;Splinter et al, 2011). In particular, while the active mouse X chromosome has an autosome-like structure, exhibiting active A and inactive B compartments and topologically associating domains (TADs), the inactive X chromosome is thought to lack compartmentalization and to solely exhibit TADs of attenuated strength .…”
Section: An Underlying A/b-like Compartmentalization Persists On the mentioning
confidence: 99%
“…Previous studies have shown that the active and inactive X chromosome have strikingly different 3D conformations (Bansal et al, 2019;Deng et al, 2015;Giorgetti et al, 2016;Minajigi et al, 2015;Nora et al, 2012;Rao et al, 2014;Splinter et al, 2011). In particular, while the active mouse X chromosome has an autosome-like structure, exhibiting active A and inactive B compartments and topologically associating domains (TADs), the inactive X chromosome is thought to lack compartmentalization and to solely exhibit TADs of attenuated strength .…”
Section: An Underlying A/b-like Compartmentalization Persists On the mentioning
confidence: 99%
“…2C,G). This evolutionarily conserved tandem repeat forms long-range CTCF-mediated chromatin loops with two other tandem repeats DXZ4 and ICCE on the Xi, and transcribes a long non-coding RNA (ncRNA) primarily from the Xa 52,53 . The three FIRRE DMPs gaining DNAme reside inside the tandem repeat, characterized by closing (“local repeat”) ATAC peaks, while probes near its major promoter decrease in DNAme (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2,3). FIRRE has been shown to form conserved Xi-specific long-range interactions with the third female-specific YY1 cluster, the macrosatellite DXZ4 which functions as a topological boundary on the Xi (reviewed in 53 ). Both of these non-coding tandem repeat loci maintain focal euchromatin on the otherwise escapeepoor long arm, and reside at the center ( FIRRE ) or periphery ( DXZ4 ) of the earliest reactivation clusters (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The superloops are not present on the Xa. Current models postulate that superloops form through loop extrusion of cohesin (Bansal et al, 2019;Bonora et al, 2018), but currently unknown is whether cohesin depletion is required to form the Xi superstructure and deposit the H3K27me3 Polycomb mark. Does cohesin binding antagonize the establishment of the Xi?…”
Section: Superloops Form Between Escapees In a Cohesin-and Polycommentioning
confidence: 99%
“…The Firre locus also normally retains its cohesins on the Xi (Fig.3E, RAD21 track) (Bonora et al, 2018;Froberg et al, 2018;Giorgetti et al, 2016). It may thereby form a superloop with Dxz4 through the retained cohesins, potentially through a cohesin-mediated loop extrusion mechanism across a 30Mb distance (Bansal et al, 2019;Bonora et al, 2018). Intriguingly, our allelic Hi-C map revealed a cohesin-dependent 'stripe' extending from Dxz4 (Fig.3D, inset).…”
Section: Superloops Form Between Escapees In a Cohesin-and Polycommentioning
confidence: 99%